A desconsideração da personalidade jurídica na empresa limitada ante a lei de liberdade econômica - Costa, Rodolfo Luiz Azevedo da (2021)
This dissertation consists of a scientific study along the lines of bibliographic research, in the field in the area of law, and will be carried out in the databases of theses and dissertations, as well as books and textbooks in general, in law colleges and universities. Identifying in the information obtained, the reflexes resulting from Provisional Measure 881/2019, converted into Law 13,874 / 2019, and its effective application of the Incident Disregard of the Legal Personality of Limited companies, and seek to identify what will be the reflexes of the Economic Freedom Law in the limited companies, knowing that three axes are identified in Law 13,874 / 2019. Firstly, it intends to create a general rule of economic law, secondly, within the scope of public law, it introduces the analysis of regulatory impact and modifies important labor rules and other measures, and thirdly, it promotes important changes in private law institutes, especially in the application of the law. Legal Personality Disregard Incident. The present dissertation intends to consider these impacts, of the law, on the life of the company and on how limited companies should behave under the new law.